GAMBARAN HEMATOLOGI MENCIT (Mus musculus) MODEL TOKSISITAS SUBKRONIS - Ita Nur Eka Pujiastuti; Sri Rahayu Lestari; Abdul Gofur (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Garlic commonly is consumed as medicine to prevent or heal illness or to maintain someone's health. Many societies prefer garlic (Allium sativum) among other herbal remedies for cholesterol treatment. It consists of several types, and one of them is single bulb garlic used to treat hypertension. There has been, however, no published research reporting the toxicological properties of single bulb garlic. The purpose of this study was to determine subchronic toxic effects of single bulb garlic administered to mice using hematological parameters. The experiment parameters were hemoglobin and hematocrit levels, the number of erythrocytes and leukocytes. Male mice (Mus musculus) strain Balb-C were treated with single bulb garlic extract for 28 days with dosage levels of 0% (N ), 0.25% (P1 ), 0.5% (P2 ), 1% (P3 ), and 2% (P4 ). Single bulb garlic showed no effect on hemoglobin and hematocrit levels but increased the number of erythrocyte and leucocyte. We concluded that single bulb garlic did not cause subchronic toxic effects.